The Influence of Mother Figure on the Thoughts of Students in Class XII at SMA PGRI 1 Lumajang Indonesia - Bopel Wasianto; Eka Ismaya Indra Purnamanita; Imam Syaifudin; Ahmad Yusthru Daswara; Rahmaniawati Rahmaniawati (International Journal Labs, 2022)
In family life, a mother has a very big role in children's education, therefore the mother is a madrasatul hall for her children. The mother figure acts as a